Micromorphology and anatomy of the cypselae of a complex of South American species in Chromolaena (Asteraceae, Eupatorieae, Praxelinae) - Queiroz, Lorena Nunes Lourenço; Christ, Anderson Luiz; Marzinek, Juliana (Phytotaxa, 2025)
Chromolaena (Eupatorieae) contains numerous species complexes and taxa with challenging delimitation and overlapping morphological characteristics. The present study aims to utilize the anatomical characteristics of the cypsela of the Chromolaena congesta complex. To achieve this objective, cypselae from the herbarium specimens were analyzed for their anatomy. The studied species exhibit characteristic features common to the tribe, subtribe, and genus, such as the presence of phytomelanin between the outer and inner mesocarp. The distribution of trichomes on the cypselae was found to be quite variable among the species, and the presence of glandular trichomes in some species helps to distinguish them from others. These features can be compared to facilitate the identification of the species in the complex.